2008
DOI: 10.1021/cr068407v
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Molecular Interactions of P. falciparum Merozoite Proteins Involved in Invasion of Red Blood Cells and Their Implications for Vaccine Design

Abstract: in 1991. The principal focus of his research at the Fundación Instituto de Inmunología de Colombia is the molecular characterization of receptor-ligand interactions between pathogenic proteins involved in invasion and their corresponding host cell receptors, mainly for P. falciparum and M. tuberculosis. He is currently candidate for a Dr. Sc. degree in chemistry at the Universidad Nacional de Colombia.Mauricio Urquiza graduated in chemistry at the Universidad Nacional de Colombia in 1991. He is currently worki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
84
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 85 publications
(85 citation statements)
references
References 444 publications
(1,524 reference statements)
0
84
0
1
Order By: Relevance
“…Of further interest, the NLR(N/K)(A/G) peptide shared by the six ORFs of P. falciparum is situated within a highly active binding peptide (Rodriguez et al, 2008), thought to interact with a glycoprotein-like receptor on the erythrocyte surface. Regardless of this intriguing similarity, it is unlikely that these five amino acids are sufficient evidence for a common evolutionary origin for all MSP3 proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Of further interest, the NLR(N/K)(A/G) peptide shared by the six ORFs of P. falciparum is situated within a highly active binding peptide (Rodriguez et al, 2008), thought to interact with a glycoprotein-like receptor on the erythrocyte surface. Regardless of this intriguing similarity, it is unlikely that these five amino acids are sufficient evidence for a common evolutionary origin for all MSP3 proteins.…”
Section: Resultsmentioning
confidence: 99%
“…Like other repetitive proteins in Plasmodium spp. (Rodriguez et al, 2008), Pv MSP-9 has extensive polymorphism in the number of motifs; however, when the repetitive motifs are aligned among them (see Rich et al, 1997) the motifs themselves accumulate more synonymous than non-synonymous substitutions (Table 4). These repeated structures in proteins often occur in linear arrays or as a superhelix (Andrade et al, 2001) such as in MSP-9.…”
Section: Discussionmentioning
confidence: 99%
“…In the search for high activity binding peptides as anti-malarial vaccine candidates (Patarroyo and Patarroyo, 2008; Rodriguez et al, 2008) it was found that peptide 20628 caused the lysis of human RBC (10.4% at 200 μM) (unpublished data). Peptide 20628 did not inhibit Gram-negative ( E. coli ATCC 25922) or Gram-positive ( S. aureus ATCC 29213) bacterial growth whilst its analog 35409 (K331A) had reduced hemolytic activity and inhibited E. coli and S. aureus bacterial growth (Maya, 2009).…”
Section: Introductionmentioning
confidence: 99%